DIDA DAN KADA DALAM BAHASA, AGAMA, SERTA KERAGAMAN BUDAYA - Roikhan Muhammad Aziz (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
Cultural diversity provides insight for expansion in Indonesian Language. It is analogous to the phenomenon of religious language which continue to search for universal values of culture and existing knowledge. Cultural language insists on diversity for grace, while thrusting religious language universality which became the foundation for the various culture.Indonesian Language will be the bridge for the universality and diversity over the faculty  of  language  and  literature  education.  It  requires  the  completion  of  Indonesian Grammatical Structure to be more compatible with the universality of religion language including the adjustment of personal pronouns as numbered one, two, and at least three persons.In Arabic Grammatical Structure, Nahwu and Shorof, person pronoun consists of single, twin, and plural. While in Indonesian Grammatical Structure only recognize personal pronoun as singular and plural. In this study of grammatical structures are using a  qualitative  approach  refers  to  the  Hahslm  method  based  on  methodology  of Sinlammim. This methodology is based on the Islam which is the foundation of Al-Quran highlights  Sura  Ali  Imran  [3]:  19  and  Al -Hijr  [15]:  87.  Required  a  nonlinear thinking  to  combine  the comparative  analysis, analogy,  and  notification  in  religion  and diversity of knowledge.Personal  pronoun  of  the  2nd  and  3rd  need  to  be  inserted  in  the  form  of  a personal pronoun which amounts of two so that the pronoun which amounts of many as a personal pronoun at least three people. With inserted pronouns 2nd person namely Kada or  You  Both  and  pronouns  3rd  person  namely  Dida  or  He/She  Both,  then  the Indonesian  have  found  a  more  universal  grammar  and  reflect  diversity.  Thus  meaning 'many' in religion can be agreed upon as 'something that amounts to at least three', It will be contributing a new grammar in search of knowledge core and cultural diversity.